Penerapan Model Kooperatif Tipe Jigsaw Untuk Meningkatkan Kualitas Pembelajaran dan Keaktifan Berbicara Siswa Kelas VII A SMP N 14 Kota Jambi - Germilasmawani Germilasmawani (Universitas Batanghari Jambi, 2019)
Speaking learning activity is still low in SMP Negeri 14 Kota Jambi.To overcome this problem researcher chooses Jigsaw cooperative learning model as an alternative to enable learners to speak.This study aims to know the successful of implementation cooperative learning model Jigsaw to improve the quality of the processes and outcomes of learning speaking participationof VIIA grade studentsSMP N 14 Jambi. This research is a classroom action research. The subjects were 32 students of class VIIA SMPN 14 Jambi. The study was conducted three cycles each cycle begins with the planning, implementation, analysis and reflection. The instruments used were observation sheet, field notes, closed questionnaire, and the performance test. Data analysis techniques of quality of process implementation of Jigsaw are done with data reduction, data display, verification and conclusion drawing, while data of learning outcomes qualitywere analyzed by using average formula. The results of the study were classified into two, namely the quality of the learning process and the quality of students’ speaking participation learning outcomes. The quality of the learning process in the first cycle and the second cycle is still low. It can be seen from the students’ low participationin speaking. But in the third cycle the quality of the learning process has been successful. From 32 students, spontaneous expression in first cycle wasonly 8, in second cyclewas16, in third cycle was 24; expressing their opinions as assigned the first cycle was 10, the second cycle was 19, the third cycle 26; responding to the opinion of friends in first cycle was 8, in second cycle was 16, in third cycle 24; asking questions first cycle 9, the second cycle 18, the third cycle 25; answering friends’ / teacher’s questions in first cycle was 10, the second cycle 18, the third cycle 25. Based on these results it can be concluded that the implementation of cooperative learning model Jigsaw can improve process quality and students’ speaking participation learning outcomes. Thus researcher suggests to the teachers to use Jigsaw cooperative model in their teaching learning process. But a classroom action research through Jigsaw model still need to be followed up with more innovative development.